Greater occipital nerve blocks in chronic cluster headache: a prospective open‐label study. (7th December 2013) - Lambru, G.; Abu Bakar, N.; Stahlhut, L.; McCulloch, S.; Miller, S.; Shanahan, P.; Matharu, M. S.
<x xml:space="preserve">Abstract</x> Background and purpose Greater occipital nerve blockade (GONB) has been shown to be effective in episodic cluster headache. However, its use in chronic cluster headache (CCH) is less certain. The study aims to prospectively assess the efficacy and consistency of response to GONB in a large series of CCH patients. Methods CCH patients who had a unilateral GONB and were referred to the National Hospital for Neurology and Neurosurgery were studied prospectively. Headache characteristics were collected using headache diaries. Responders were considered to be patients with a complete or partial response lasting at least 7 days. In a subgroup of responders the outcomes of serial GONB performed at 3‐monthly intervals were also analysed. Results Eighty‐three CCH patients were studied. After the first GONB, a positive response was observed in 47 (57%) patients: 35 (42%) were rendered pain free, 12 (15%) had a partial benefit and one patient obtained <50% improvement. The duration of a positive response lasted a median of 21 days (range 7–504 days). There was a transient worsening of condition in 6% of patients. The overall rate and average duration of response remained consistent after the second [n = 37; 31 responders (84%); median duration 21 days], third [n = 28; 20 responders (71%); median duration 25 days] and fourth [n = 14; 10 responders (71%); median duration 23 days] injections. Conclusion GONB seems to be an efficacious treatment with reproducible effects in CCH patients. Performed three monthly, GONB may have a useful role in the management of CCH.